The Longoria affair [videorecording (DVD)] - Plana, Tony, 1952- (PBS, 2010)
A documentary on the Mexican-American civil rights movement. The film tells the story of one key injustice, the refusal, by a small-town funeral home in Texas after World War II, to care for a dead soldier's body 'because the whites wouldn't like it,' and shows how the incident sparked outrage nationwide and contributed to the Voting Rights Act of 1965.